Methods of Laser Spectroscopy in Devices for Continuous Monitoring of O2 and CO Content in Boiler Smoke Gases - V. A. Firago; V. Wujcik; I. S. Manak; P. Komada; V. V. Krot (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Application efficiency of various absorption laser spectroscopy methods for determination of gas component concentration in boiler smoke gases has been studied in the paper, O2 and CO absorption spectra have been analyzed, optimum absorption lines in near IR spectral range (about 0.76 µm for O2 and 1.56 µm for CO) have been selected and graphical dependences of intensity and half-width of the selected lines on the investigated medium temperature and pressure have been shown. Processes of monitoring CO and O2 content in boiler smoke gases while using basic laser spectroscopy methods have been simulated and measuring errors have been analyzed. It has been found out that in order to decrease methodical errors of concentration measuring it is necessary to take into account the investigated medium temperature and pressure. The paper shows that the least errors of continuous CO and O2 concentration monitoring at the presence of variations in dissipative losses have been ensured by the modified correlation method though its threshold sensitivity is less than integral and correlation ones.